Respuesta :
i can help!!
Let's solve your equation step-by-step.
3(x+5)=2(3x+12)
Step 1: Simplify both sides of the equation.3(x+5)=2(3x+12)
(3)(x)+(3)(5)=(2)(3x)+(2)(12)(Distribute)
3x+15=6x+24
Step 2: Subtract 6x from both sides.3x+15−6x=6x+24−6x
−3x+15=24
Step 3: Subtract 15 from both sides.
−3x+15−15=24−15
−3x=9
Step 4: Divide both sides by -3.
−3x−3=9−3
x=−3
Answer:x=−3
Hope this helps!!
Let's solve your equation step-by-step.
3(x+5)=2(3x+12)
Step 1: Simplify both sides of the equation.3(x+5)=2(3x+12)
(3)(x)+(3)(5)=(2)(3x)+(2)(12)(Distribute)
3x+15=6x+24
Step 2: Subtract 6x from both sides.3x+15−6x=6x+24−6x
−3x+15=24
Step 3: Subtract 15 from both sides.
−3x+15−15=24−15
−3x=9
Step 4: Divide both sides by -3.
−3x−3=9−3
x=−3
Answer:x=−3
Hope this helps!!
Expand 3(x + 5): 3x + 15
Expand 2(3x + 12): 6x + 24
3x+ 15=6x + 24
then, subtract 15 from both sides
Simplify,
3x= 6x + 9
subtract 6x from both sides
3x - 6x= 6x + 9 - 6x
Simplify,
-3x=9
divide both sides by -3
-3x/-3 = 9/-3
Simplify,
x= -3, which is the final answer
Expand 2(3x + 12): 6x + 24
3x+ 15=6x + 24
then, subtract 15 from both sides
Simplify,
3x= 6x + 9
subtract 6x from both sides
3x - 6x= 6x + 9 - 6x
Simplify,
-3x=9
divide both sides by -3
-3x/-3 = 9/-3
Simplify,
x= -3, which is the final answer